2010
DOI: 10.2522/ptj.20090363
|View full text |Cite
|
Sign up to set email alerts
|

Detectable Changes in Physical Performance Measures in Elderly African Americans

Abstract: The SEMs were similar to previously reported values and can be used when working with African American and white older adults. Estimates of MDC were calculated to assist in clinical interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 35 publications
3
54
3
4
Order By: Relevance
“…Acceptable reliability and validity of the test have been demonstrated among community-dwelling elderly people [27]. Several studies [28] have recognized 1.0 m/s to be the cut-off value for adverse outcomes while an increase of 0.19 m/s has been documented [25] as a clinically relevant change for elderly people.…”
Section: Primary Outcome: Mobilitymentioning
confidence: 97%
See 2 more Smart Citations
“…Acceptable reliability and validity of the test have been demonstrated among community-dwelling elderly people [27]. Several studies [28] have recognized 1.0 m/s to be the cut-off value for adverse outcomes while an increase of 0.19 m/s has been documented [25] as a clinically relevant change for elderly people.…”
Section: Primary Outcome: Mobilitymentioning
confidence: 97%
“…The improvements in mean shift ranged from 13% to 33%. At the final assessment, four participants (numbers 1, 2, 3 and 5) performed better than average for very old women [24] and four participants (numbers 1, 2, 4 and 6) obtained clinically relevant improvements in TUG (!4 s) [25] with a decrease in time to perform the test ranging from 4 to 12.5 s (Table 3). Furthermore, all except participant number 3 improved their walking speed significantly by 11% to 59% (mean shift) and half of the participants had a comfortable walking speed exceeding the cut-off for adverse outcome of 1 m/s at the final assessment.…”
Section: Changes In the Mobility And Functional Strength Outcomes: Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Our largest MDC found in TUAG (1.912s) is small when compared to other literature reporting 3.5s in Parkinson's disease and in older adults [33,34]. Our small MDC is in keeping with the decision to report on repeated measurements of the same events; other studies used repeated patient measurements introducing realistic, but nonetheless greater variation.…”
Section: Precisionmentioning
confidence: 46%
“…Mangione et al [23] reported that TUG tests were decreased after performing progressive resistant exercises using an elastic band of older adults. Park et al [24] reported that strengthening exercise programs in the rural elderly population resulted in a decrease in TUG scores (from 9.8 to 9.0 sec).…”
Section: Discussionmentioning
confidence: 99%